2004
DOI: 10.1381/0960892042387066
|View full text |Cite
|
Sign up to set email alerts
|

Duodenal Switch is a Safe Operation for Patients who have Failed Other Bariatric Operations

Abstract: In patients in whom gastroplasty, gastric bypass or both have failed to provide adequate weight loss, or worse have resulted in complications, DS can be performed as a safe revisional operation. The revision of other failed bariatric operations to DS results in both weight loss and resolution of the complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
6

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(50 citation statements)
references
References 18 publications
1
43
0
6
Order By: Relevance
“…DS is another interesting option in this patient population, but larger series are still needed [7,10,12,16,18,30]. Because of the superior weight loss seen with the DS when compared to other bariatric procedures, interest has grown in using this procedure in the treatment of morbidly obese patients who fail in other surgical therapy [16,18,23]. The DS was first used as a revisional therapy in 2001 to treat a patient who had undergone VBG in the past, and was still suffering from diabetes mellitus and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…DS is another interesting option in this patient population, but larger series are still needed [7,10,12,16,18,30]. Because of the superior weight loss seen with the DS when compared to other bariatric procedures, interest has grown in using this procedure in the treatment of morbidly obese patients who fail in other surgical therapy [16,18,23]. The DS was first used as a revisional therapy in 2001 to treat a patient who had undergone VBG in the past, and was still suffering from diabetes mellitus and obesity.…”
Section: Discussionmentioning
confidence: 99%
“…Destes pacientes dumpers graves, todos demonstravam reganho de peso, contradizendo a idéia frequente de que o dumping colaboraria para a perda de peso 19 . Zimmerman demonstrou, em um estudo comparativo do bypass gástrico com a gastroplastia vertical, uma ocorrência de 50% de síndrome de dumping em pacientes com bypass gástrico que insistiam na ingestão de doces, e que foram tratados satisfatoriamente com a orientação dietética 20 .…”
Section: Resultados Resultados Resultados Resultados Resultadosunclassified
“…On the other hand, revisional RYGB has been shown to be a safe procedure with post-operative complication rates comparable to the primary RYGB [4, 19, 21,32,35]. Keshishian and colleagues [36] indicated that conversion to duodenal switch brings an increased risk of complications. Nevertheless, research is still limited regarding this type of conversion surgery.…”
Section: Outcomes After Reoperative Bariatric Surgery Medical Complicmentioning
confidence: 99%
“…Then, continuing on page 2710, the entries in the first column should be [27], [28], [29]; [30], [31], [32], [35], [36], [34], [37], [38], [39], [41], [42], and [43].…”
Section: Behavioral and Psychosocial Variables In Reoperative Bariatrmentioning
confidence: 99%